2020
DOI: 10.1002/ece3.6137
|View full text |Cite
|
Sign up to set email alerts
|

Population modelling and genetics of a critically endangered Madagascan palm Tahina spectabilis

Abstract: Madagascar is home to 208 indigenous palm species, almost all of them endemic and >80% of which are endangered. We undertook complete population census and sampling for genetic analysis of a relatively recently discovered giant fan palm, the Critically Endangered Tahina spectablis in 2008 and 2016. Our 2016 study included newly discovered populations and added to our genetic study. We incorporated these new populations into species distribution niche model (SDM) and projected these onto maps of the region. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…However, some species may disperse in a fashion that leads to isolated founder plants that can establish new populations, if local environmental conditions are suitable (Shapcock et al, 2020). Given that four of the five species considered here are common in the nursery trade, it is possible that individuals planted in gardens outside of the native range may act facilitate naturalization for future generations, similar to the pattern observed for Trachycarpus fortunei in Switzerland (Fehr & Burga, 2016) and eight invasive palm species in Panama (Svenning, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, some species may disperse in a fashion that leads to isolated founder plants that can establish new populations, if local environmental conditions are suitable (Shapcock et al, 2020). Given that four of the five species considered here are common in the nursery trade, it is possible that individuals planted in gardens outside of the native range may act facilitate naturalization for future generations, similar to the pattern observed for Trachycarpus fortunei in Switzerland (Fehr & Burga, 2016) and eight invasive palm species in Panama (Svenning, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…To be consistent with field data, we based our models on a 10‐year time step. Using long‐time intervals relies on the assumption that the species is slow‐growing and has low reproductive output, so few changes would occur in populations within a year (Hayward et al., 2021; Osunkoya, 2003; Shapcott et al., 2020; Shimizu‐Kimura, Burnett, & Shapcott, 2017). Using this assumption, we approximated the gaps between two surveys to 10 years, although some were one or 2 years longer.…”
Section: Methodsmentioning
confidence: 99%
“…Since a new cluster of plants was discovered in 2011 in GR3, we only used the part of GR3 that had been consistently surveyed every year to estimate rates. Fecundity was estimated as the number of surviving seedlings produced per individual of a given class in a 10‐year time step (Hayward et al., 2021; Shapcott et al., 2020). Fecundity rates giving juveniles (F 1i for class i ) take both sexual and vegetative reproduction into account.…”
Section: Methodsmentioning
confidence: 99%
“…& Rakotoarin. in Madagascar (Shapcott et al, 2007;Shapcott et al, 2020) have shown that the re-introduction of genetically diverse individuals from other populations will reduce the risk of inbreeding. While it is important to maintain the unique genetic diversity of each population, humanmediated disturbances have disrupted the natural processes maintaining this diversity and the risk of outbreeding depression is unwarranted (Frankham et al, 2011).…”
Section: Gene Flow and Potential Conservation Actionsmentioning
confidence: 99%